O princípio da equidade na forma de participação no custeio - Alcântara, Marcelino Alves de (2010)
This paper aims to address the main, accurate and scientific rigor, the principle (or goal) of the Social Security System, in the form of equity participation in funding, which comes under art. 194, sole paragraph, item V of the Charter of the Federative Republic of Brazil in 1988. To be able to achieve the ideologies of welfare and social justice (the ultimate goals of the Social Order), mister you do garnish the Social Security system of financial resources to its fundamental mission. Meanwhile, legislators shaped the text of the Standard Basic goals (principles) specific rules governing the financing model of security, including the equity in the form of participation in the costs. Thus, this paper seeks to identify correctly in relation to the subject, its definition, nature, its constitutional foundations, its own characteristics and those shared with any other character of law, with the field of exploration for legal interpretation of the rules extracted from positive law, especially the Federal Constitution